2000
DOI: 10.1603/0022-2585-37.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <I>Ehrlichia chaffeensis</I> (Rickettsiales: Rickettsiaceae) in <I>Amblyomma americanum</I> (Acari: Ixodidae) from the Georgia Coast and Barrier Islands

Abstract: Human monocytic ehrlichiosis is an emerging zoonosis caused by infection with Ehrlichia chaffeensis Anderson, Dawson, Jones & Wilson, which is transmitted to mammals by ixodid ticks. Prevalence of infected ticks and distribution of infection foci indicate relative risk of human exposure to ehrlichiosis and may be influenced by factors such as geographic isolation, human disturbance, and the availability of suitable mammalian reservoir hosts. To test, this, individual and pooled lone star ticks, Amblyomma ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
0
25
2
3
Order By: Relevance
“…In those studies, the prevalence of infected ticks was reported to be 0 to 29% in the United States (2,4,22,26). The results of our current study, however, suggest that the prevalence rates of positive ticks may be greater if this nested RT-PCR is used.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In those studies, the prevalence of infected ticks was reported to be 0 to 29% in the United States (2,4,22,26). The results of our current study, however, suggest that the prevalence rates of positive ticks may be greater if this nested RT-PCR is used.…”
Section: Discussioncontrasting
confidence: 69%
“…This method has been used to increase the sensitivity for detection of E. chaffeensis in infected cell cultures and in blood, tissue, and naturally infected tick specimens (8,15,26,27). Wen et al (25) reported that, by using serially diluted DNA from purified E. canis, as little as 0.2 pg of E. canis DNA could be detected by the nested PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generic primers detect many of the organisms in related genus groups, while specific primers designed to amplify highly variable portions of the genome can be chosen to identify only a particular species of organism (BREITSCHWERDT et al, 1998). The PCR protocol widely employed to detect E. canis is the 16S rRNA nested-PCR, but limited sequence variation of this gene between related bacteria results in unspecific amplification (SUMNER et al, 1997;WHITLOCK et al, 2000). A highly sensitive and specific real-time PCR was used, targeting the Ehrlichia disulfide bond formation protein (dsb) gene, which was identical to the corresponding sequence of the North American isolate (LABRUNA et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although few human cases have been described (23,31,35,41), Anaplasma strains have been detected in Ixodes ricinus ticks collected in different countries of Western Europe (5,7,14,17,22,32,34,38). The genus Ehrlichia includes the agent of human monocytic ehrlichiosis (Ehrlichia chaffeensis), mainly transmitted by Amblyomma americanum in the United States (11,15,43), and other species, mostly involved in animal infections. To our knowledge, just two human cases have been reported in Europe, based only on serologic evidence (26,33).…”
mentioning
confidence: 99%